1997
DOI: 10.1109/96.641510
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterization of solder pastes for surface mount applications

Abstract: Accurate rheological measurements are needed in order to correlate the rheological behavior of solder pastes to their performance in the surface mount technology (SMT) process. In this paper, we summarize our efforts to measure the rheological properties of solder pastes, and outline the difficulties in obtaining their true rheological properties. In particular, we show that the rheological measurements of solder pastes are affected by "slip" at the test-apparatus surfaces and by shear fracture within the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The drop in viscosity could have been due to the sample fracturing either at the interface or at the bulk material. A previous study by Kolli et al (1997) on solder pastes, observed internal slip in the bulk of the solder paste sample about midway between the gap heights, ultimately leading to the expulsion of part of the sample. The author also found that the time at which this internal slip occurred was approximately ten seconds after the test was underway and thereafter, shear fracture was observed to take place in the samples.…”
Section: Effect Of Surface Roughness Of Parallel Plate Geometry On Thmentioning
confidence: 93%
See 1 more Smart Citation
“…The drop in viscosity could have been due to the sample fracturing either at the interface or at the bulk material. A previous study by Kolli et al (1997) on solder pastes, observed internal slip in the bulk of the solder paste sample about midway between the gap heights, ultimately leading to the expulsion of part of the sample. The author also found that the time at which this internal slip occurred was approximately ten seconds after the test was underway and thereafter, shear fracture was observed to take place in the samples.…”
Section: Effect Of Surface Roughness Of Parallel Plate Geometry On Thmentioning
confidence: 93%
“…The formation of wall-slip is usually seen as a source of error in the rheological measurements and various steps have been taken to eliminate or reduce wall-slip (Kolli et al 1997). However, in some cases the wall-slip is important because most material production involves flow through some form of complex geometry which is surrounded by walls.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used method to capture the rheological behaviour is through a shear/hysteresis loop test, which entails viscosity measurements where the shear rate increases from a minimum to a maximum value and then returns back to the minimum. The hysteresis loop test has been used to measure the thixotropic behaviour of the solder paste in Kolli et al ’s (1997) and Durairaj et al ’s (2004) studies. This measurement does not provide sufficient time for the viscosity to reach a steady value.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…(16)(17)(24)(25)(26) Among the surprising phenomena observed during the flow of these multi-phase materials, the wall depletion effect (apparent slip at the wall) is probably one of the most important. (27) Kalyon et al (27) have shown that the contribution of slip to the overall flow rate is negligible in a given range of shear stress, depending on the behavior of the material (shear thinning or thickening).…”
Section: Characterization Of a Concentrated Suspension Using The Penementioning
confidence: 99%